2016
DOI: 10.14740/jnr404w
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Clinico-Biochemical Profile of Neonatal Seizure

Abstract: Background: Seizure is the most frequent sign of neurologic dysfunction in the neonate. Biochemical disturbances occur frequently in neonatal seizures either as an underlying cause or as associated abnormalities. In their presence, it is difficult to control seizures and there is a risk of further brain damage. Early recognition and treatment of biochemical disturbances are essential for optimal management and satisfactory long-term outcome. The aims were to study the biochemical abnormalities in neonatal seiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 10 publications
5
11
0
Order By: Relevance
“…Out of it, 115 neonates had episodes of neonatal seizures (9.6%). 6 In majority (46.61%) of the cases subtle seizures were noted as the commonest type of seizure followed by tonic and clonic, which share the same results with study done by Su-Ching Hu and Kun-Long Hung in Cathay General Hospital, Taipei in 2015, Subtle seizures were 77.2% followed by tonic (13.7%) and clonic (9.1%) seizures. 4 In a study by Arun Kumar A, 7 Subtle seizures were the commonest (38%) while tonic, clonic, myoclonic and combined seizures constituted 30%, 19%, 2% and 11% respectively, Das et al in 2015 also found among 115 neonates subtle seizures in 49 (42.6%) followed by tonic 39 (33.9%) and clonic 10 (8.7%).…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…Out of it, 115 neonates had episodes of neonatal seizures (9.6%). 6 In majority (46.61%) of the cases subtle seizures were noted as the commonest type of seizure followed by tonic and clonic, which share the same results with study done by Su-Ching Hu and Kun-Long Hung in Cathay General Hospital, Taipei in 2015, Subtle seizures were 77.2% followed by tonic (13.7%) and clonic (9.1%) seizures. 4 In a study by Arun Kumar A, 7 Subtle seizures were the commonest (38%) while tonic, clonic, myoclonic and combined seizures constituted 30%, 19%, 2% and 11% respectively, Das et al in 2015 also found among 115 neonates subtle seizures in 49 (42.6%) followed by tonic 39 (33.9%) and clonic 10 (8.7%).…”
Section: Resultssupporting
confidence: 84%
“…8 Nawab T et al, Arun Kumar et al and D Das et al also found similar results where the most common aetiology for seizure was hypoxic -ischemia 60%, 44% and 56% respectively, followed by sepsis 22.7%, 30% and 21% respectively. 6,7,9 CONCLUSION Neonatal seizure is a commonly seen disorder in hospitalized new born with incidence of 11.3%, predominantly in term, male newborns and mostly seen on the first day of life with subtle type as described in this study. The most common aetiology being HIE as seen in 69 cases followed by sepsis and biochemical abnormalities.…”
Section: > 7 Days Totalsupporting
confidence: 54%
See 1 more Smart Citation
“…Similar observation were seen in study by Aziz et al [4] where term babies constitutes 65% and preterm 35%. In studies by Park Weon et al [5] and Dinesh Das et al [6] ,they also reported a much higher incidence in term babies compared to preterm neonates. In my study, neonatal seizures were common in male babies contributing about 56.25% and female about 43.75%, similar to study done by Aziz et al [4] (male 60%, female 40%) and Dinesh Das et al [6] (male 62.6%, female37.4%) also reported male predominance.…”
Section: Resultsmentioning
confidence: 99%
“…Neonatal seizures are a common neurological problem with a frequency of 1.5-14/ 1000 neonates. The seizures in neonates may manifest as paroxysmal alteration in motor, sensory, behavioral or autonomic dysfunctions [2]. Clinically, there are four seizure types: subtle, clonic, tonic, and myoclonic.…”
Section: Introductionmentioning
confidence: 99%